A Review of Recent Studies on the Antioxidant and Anti-Infectious Properties of Senna Plants. (4th February 2022) - Alshehri, Mohammed M.; Quispe, Cristina; Herrera-Bravo, Jesús; Sharifi-Rad, Javad; Tutuncu, Sena; Aydar, Elif Feyza; Topkaya, Cansu; Mertdinc, Zehra; Ozcelik, Beraat; Aital, Mahima; Kumar, N. V. Anil; Lapava, Natallia; et al.
Abstract : The use of phytochemicals is gaining interest for the treatment of metabolic syndromes over the synthetic formulation of drugs. Senna is evolving as one of the important plants which have been vastly studied for its beneficial effects. Various parts of Senna species including the root, stem, leaves, and flower are found rich in numerous phytochemicals. In vitro, in vivo, and clinical experiments established that extracts from Senna plants have diverse beneficial effects by acting as a strong antioxidant and antimicrobial agent. In this review, Senna genus is comprehensively discussed in terms of its botanical characteristics, traditional use, geographic presence, and phytochemical profile. The bioactive compound richness contributes to the biological activity of Senna plant extracts. The review emphasizes on the in vivo and in vitro antioxidant and anti-infectious properties of the Senna plant. Preclinical studies confirmed the beneficial effects of the Senna plant extracts and its bioactive components in regard to the health-promoting activities. The safety, side effects, and therapeutic limitations of the Senna plant are also discussed in this review. Additional research is necessary to utilize the phenolic compounds towards its use as an alternative to pharmacological treatments and even as an ingredient in functional foods.